Assessment of the bioprotective potential of lactic acid bacteria against Listeria monocytogenes in ground beef - Gomez, Johana Stefani (2021)
Lactic acid bacteria can be considered as natural biopreservative and good biotechnological alternative to food safety. In this study, the antilisterial compounds produced by Enterococcus isolates from the Patagonian environment and their effectiveness for the control of Listeria monocytogenes in a food model were studied. Enterococcus isolates whose cell-free supernatant presented activity against Listeria monocytogenes were identified and evaluated for their virulence factors. The activity of the antimicrobial compounds produced by Enterococcus sp. against Listeria monocytogenes Scott A in meat gravy and ground beef during refrigerated storage was tested. The results indicated that ten Enterococcus isolates presented activity against Listeria monocytogenes and none of the selected strains presented virulence factors. L. monocytogenes in the food models containing the antilisterial compounds produced by Enterococcus sp. has decreased over the days, indicating that these compounds and cultures are an alternative to control the growth of L. monocytogenes in foods.